Isotope analysis of human dental calculus δ13CO32−: Investigating a potential new proxy for sugar consumption. (25th March 2022) - Chidimuro, Blessing; Mundorff, Amy; Speller, Camilla; Radini, Anita; Boudreault, Noémie; Lucas, Mary; Holst, Malin; Lamb, Angela; Collins, Matthew; Alexander, Michelle
Abstract : Rationale: Dental calculus (mineralised dental plaque) is composed primarily of hydroxyapatite. We hypothesise that the carbonate component of dental calculus will reflect the isotopic composition of ingested simple carbohydrates. Therefore, dental calculus carbonates may be an indicator for sugar consumption, and an alternative to bone carbonate in isotopic palaeodiet studies. Methods: We utilised Fourier transform infrared attenuated total reflectance analysis to characterise the composition and crystallisation of bone and dental calculus before isotope analysis of carbonate. Using a Sercon 20‐22 mass spectrometer coupled with a Sercon GSL sample preparation system and an IsoPrime 100 dual inlet mass spectrometer plus Multiprep device to measure carbon, we tested the potential of dental calculus carbonate to identify C4 resources in diet through analysis of δ 13 C values in paired bone, calculus and teeth mineral samples. Results: The modern population shows higher δ 13 C values in all three tissue carbonates compared to both archaeological populations. Clear differences in dental calculus δ 13 C values are observed between the modern and archaeological individuals suggesting potential for utilising dental calculus in isotope palaeodiet studies. The offset between dental calculus and either bone or enamel carbonate δ 13 C values is large and consistent in direction, with no consistent offset between the δ 13 C values for the three tissues per individual. Conclusions: Our results support dental calculus carbonate as a new biomaterial to identify C4 sugar through isotope analysis. Greater carbon fractionation in the mouth is likely due to the complex formation of dental calculus as a mineralized biofilm, which results in consistently high δ 13 C values compared to bone and enamel.